Structural stability and electronic properties of graphene/germanene heterobilayer - Hamid, Mohamad Amin; Chan, Kar Tim; Raymond Ooi, Chong Heng; Zainuddin, Hishamuddin; Mohd Shah, Nurisya; Shahrol Nidzam, Nazirul Nazrin (Elsevier BV, 2021)
In this work, the structural and electronic properties of graphene/germanene heterobilayer is investigated by using density functional theory. We find that the graphene and germanene are bounded together mainly by weak van der Waal forces. This is supported by small interlayer binding energy of graphene/germanene heterobilayer. In the heterobilayer, the Dirac cone characteristics of both graphene and germanene layers are well preserved. The band gap opening is found due to the unsaturated pz-orbital of germanene layer. Further variation of compressive strain along the normal of the heterobilayer increases the band gap opening in the heterobilayer. Inhomogeneous charge redistribution is found in between graphene and germanene layer, where small charge accumulation region is found in germanene layer while charge depletion region in graphene layer. The total charge accumulations in between graphene and germanene sheets is 5.645 × 10−4 .